2021
DOI: 10.1038/s41598-021-85598-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of head and neck cancer in patients with peptic ulcers and the effect of Helicobacter pylori treatment

Abstract: It remained inconclusive whether patients with peptic ulcer disease had a higher risk of head and neck cancer (HNC). Therefore, we enrolled 109,360 patients with peptic ulcer disease and matched for age and sex with 218,720 controls from the Taiwan National Health Insurance Research Database between January 1, 1997 and December 31, 2013.The HNC incidence rate was 1.33-fold higher in the peptic ulcer group than in the control group (7.52 vs. 5.68 per 100,00 person-years; crude relative risk: 1.33; 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Their results showed that peptic ulcer disease was closely related to the increased incidence of laryngeal cancer and hypopharyngeal cancer. Helicobacter pylori treatment may help prevent HNC in patients with peptic ulcer disease (49). Whether bacterial infection increases the occurrence of laryngeal cancer or leads to a poor prognosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that peptic ulcer disease was closely related to the increased incidence of laryngeal cancer and hypopharyngeal cancer. Helicobacter pylori treatment may help prevent HNC in patients with peptic ulcer disease (49). Whether bacterial infection increases the occurrence of laryngeal cancer or leads to a poor prognosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of PUD was based on either a discharge diagnosis of PUD or a diagnosis of PUD confirmed at least twice in an outpatient department by gastroenterologists with a prescription involving proton pump inhibitors (PPIs). This definition has been used in previous studies 18,19 . To ensure that the PUD was incident during the follow‐up period, we excluded participants with pre‐existing PUD before newly diagnosis of SD.…”
Section: Methodsmentioning
confidence: 99%
“…This definition has been used in previous studies. 18,19 To ensure that the PUD was incident during the follow-up period, we excluded participants with pre-existing PUD before newly diagnosis of SD. We also excluded those who used PPIs or H2 blockers within 3 months before SD diagnosis.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…NHIRD is available for research purposes with appropriate applications. The validity of NHIRD for use in epidemiological cancer research has been shown in the previous publication (17)(18)(19)(20)(21)(22)(23)(24). NHIRD includes patients treated at dedicated veterans' hospitals.…”
Section: Data Sourcesmentioning
confidence: 97%